Biochemistry explained : a practical guide to learning biochemistry - Millar, Thomas (Routledge/Taylor & Francis, 2002)
"Biochemistry Explained employs an innovative approach which has proven highly successful in the author's own classes. Information is presented in a clear and manageable way so that learning becomes simple - even fun! Emphasis is placed on establishing a thorough understanding of the foundations of and common linkages between molecular structures and reactions, so that eventual interpretation of complex biochemical pathways and reactions is easy. All of the major molecular structures and biochemical pathways are covered, and, for the most part, these centre on mammalian biochemistry." "This textbook will serve as an invaluable resource for any student who is struggling with the standard texts, and for postgraduate students who need to refresh their knowledge quickly."--BOOK JACKET.